Attitudes, Anxiety, Skills and Culture in Research: The Case of a Private Higher Education Institutions - Eric S Parilla; Arestday Dagani; Ruby Ann Suguitan (Research Synergy Foundation, 2023)
This study is about research attitudes, anxiety, skills and culture of private higher education institutions. Universities and colleges seek to cultivate and develop students. Their primary responsibilities are to provide quality education and substantially contribute to society. Moreover, the university should have a strong research culture to attain these goals. The study participants are full-time faculty members of the institution, and descriptive statistics and partial least squares are used to analyze data. The HEI under investigation showed a positive attitude towards research because the institution encourages its faculty members to do research activities. They also have moderate competence skills and are anxious about research activities. On the other hand, the dominant research culture is constructive, and a supportive research environment characterizes it. According to the results of PLS-SEM, research skills are significantly related to research culture. Thus, the university should continuously upgrade its research skills to develop its research culture.